2019
DOI: 10.1186/s12864-019-5529-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide data from the Bubi of Bioko Island clarifies the Atlantic fringe of the Bantu dispersal

Abstract: Background Bioko is one of the few islands that exist around Africa, the most genetically diverse continent on the planet. The native Bantu-speaking inhabitants of Bioko, the Bubi, are believed to have colonized the island about 2000 years ago. Here, we sequenced the genome of thirteen Bubi individuals at high coverage and analysed their sequences in comparison to mainland populations from the Gulf of Guinea. Results We found that, genetically, the closest mainland popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Several ancient DNA (aDNA) studies have shown that the overall genetic structure was shaped by three ancestral and over-imposed genomic components respectively deriving from the Mesolithic hunter-gatherers, the Early Neolithic farmers, and the steppe nomads that entered Europe from the East around 5,000 years ago 3-7 . However, it is expected that the genetic homogenisation of the European populations during the last two millennia complicates our ability to discern subtle changes in ancestry by using some common population genetic tools.Complementary to these analyses, the distribution of so-called identity by descent (IBD) genomic stretches, which are co-inherited genetic segments delimited by recombination events, can provide information on more recently shared ancestry among individuals [8][9][10] . Such genomic block characterization in current populations has demonstrated the presence of co-ancestry across geographically distant Europeans shared over the last few thousand years, and revealed more recently shared co-ancestry in neighboring populations 11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several ancient DNA (aDNA) studies have shown that the overall genetic structure was shaped by three ancestral and over-imposed genomic components respectively deriving from the Mesolithic hunter-gatherers, the Early Neolithic farmers, and the steppe nomads that entered Europe from the East around 5,000 years ago 3-7 . However, it is expected that the genetic homogenisation of the European populations during the last two millennia complicates our ability to discern subtle changes in ancestry by using some common population genetic tools.Complementary to these analyses, the distribution of so-called identity by descent (IBD) genomic stretches, which are co-inherited genetic segments delimited by recombination events, can provide information on more recently shared ancestry among individuals [8][9][10] . Such genomic block characterization in current populations has demonstrated the presence of co-ancestry across geographically distant Europeans shared over the last few thousand years, and revealed more recently shared co-ancestry in neighboring populations 11 .…”
mentioning
confidence: 99%
“…Complementary to these analyses, the distribution of so-called identity by descent (IBD) genomic stretches, which are co-inherited genetic segments delimited by recombination events, can provide information on more recently shared ancestry among individuals [8][9][10] . Such genomic block characterization in current populations has demonstrated the presence of co-ancestry across geographically distant Europeans shared over the last few thousand years, and revealed more recently shared co-ancestry in neighboring populations 11 .…”
mentioning
confidence: 99%
“…During the first half of the 16th century, the archipelago of São Tomé and Príncipe, located in the Gulf of Guinea (1 • N, 7 • E), became one of the first examples of the so-called "plantation complex", which was soon to take over the New World [1] (Figure 1a). When the Portuguese reached the Gulf of Guinea in the early 1470s, they found the islands of São Tomé (860 km 2 ), Príncipe (136 km 2 ) and Annobón (17 km 2 ) to be uninhabited. A fourth island, Fernando Pó (now Bioko), located only 32 km off the coast of Cameroon, had already been populated by the Bubi, an autochthonous Bantu-speaking group who had presumably reached its shores by canoe [2].…”
Section: Introductionmentioning
confidence: 99%
“…When the Portuguese reached the Gulf of Guinea in the early 1470s, they found the islands of São Tomé (860 km 2 ), Príncipe (136 km 2 ) and Annobón (17 km 2 ) to be uninhabited. A fourth island, Fernando Pó (now Bioko), located only 32 km off the coast of Cameroon, had already been populated by the Bubi, an autochthonous Bantu-speaking group who had presumably reached its shores by canoe [2]. While São Tomé and Príncipe were both settled in the last decade of the 15th century, the permanent settlement of Annobón only started in the mid-16th century, and the island always remained sparsely populated until it was ceded to Spain, together with Bioko, in 1778.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation